ANALISIS MATERI E-BOOK AL-MUMTAZ JILID I DALAM PENERAPAN PEMBELAJARAN BAHASA ARAB UNTUK SISWA TK B - Noor, Aulia Fathimah; Candrawangi, Rizki; Qory, Dinda Latifah; Ashfiyah, Ashfiyah (Prosiding Konferensi Nasional Bahasa Arab, 2023)
This research uses qualitative methods in the form of data analysis from the books presented. This research aims to explain the definition of an ebook and its benefits, the definition of early childhood education, as well as an analysis of the ebook in terms of the main coverage of the material content, and students' ability to use the book. From this research it can be concluded that this book is not suitable to be presented to Kindergarten B students. This is because the coverage of the discussion of the material presented is heavy and too difficult to apply in Arabic language learning for Kindergarten B students. Apart from that, the vocabulary presented in This book is too difficult to apply to Kindergarten B students. For this reason, it is necessary to develop the material in this book so that it can be distributed and presented to Kindergarten B students.